Ion Kinetics in Thin Current Sheets at Lunar Distances - S. R. Kamaletdinov; A. V. Artemyev; A. Runov; V. Angelopoulos (Geophysical Research Letters)
Abstract The magnetotail current sheet plays a crucial role in substorm dynamics, affecting the entire magnetosphere. Formation and reconnection of thin (ion‐gyroscale) current sheets initiate magnetospheric substorms. Theoretical models suggest that a transient, demagnetized ion population is key element of the thin current sheet configuration. At lunar distances, the magnetotail provides a unique opportunity for in situ investigation of this population due to the high fraction of hot demagnetized ions. Using observations of thin current sheets by the Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun mission, we show that the relative drift between demagnetized hot ions and magnetized cold ions, likely driven by a strong polarization electric field, reduces the ion current density to nearly zero in the spacecraft rest frame. Hot ions exhibit a crescent‐like velocity distribution, contributing to ion agyrotropy. We discuss this population in the context of advanced thin current sheet models, including transient ions performing Speiser‐like motion. These observations provide valuable insights for numerical and theoretical studies.